2020
DOI: 10.1371/journal.pmed.1003061
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare factors associated with the risk of antepartum and intrapartum stillbirth in migrants in Western Australia (2005-2013): A retrospective cohort study

Abstract: Background Migrant women, especially from Indian and African ethnicity, have a higher risk of stillbirth than native-born populations in high-income countries. Differential access or timing of ANC and the uptake of other services may play a role. We investigated the pattern of healthcare utilisation among migrant women and its relationship with the risk of stillbirth (SB)-antepartum stillbirth (AnteSB) and intrapartum stillbirth (IntraSB)-in Western Australia (WA). Methods and findings A retrospective cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Genealogical linkage through the Family Connections Linkage Facility of the WADLS [25] was used to link mothers with child records. The details of the datasets used were described elsewhere [6,19].…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Genealogical linkage through the Family Connections Linkage Facility of the WADLS [25] was used to link mothers with child records. The details of the datasets used were described elsewhere [6,19].…”
Section: Data Sourcesmentioning
confidence: 99%
“…Similar research is limited in Australia and the impact of acculturation on stillbirth risk is poorly understood; we have previously shown that the migrant population, compared with the Australian-born population, utilise healthcare services differently. Late commencement of antenatal-care visits and lack of access to or uptake of doctorprovided intrapartum-care as well as absence of private health insurance emerged as underlying factors for increased risk of stillbirth in specific ethnic groups in Western Australia (WA) [19]. However, it is not clear whether the risk of stillbirth persists the longer migrants live and interact with the community in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics of the selected studies have been outlined in Table 1 . The studies were conducted in Europe ( n = 37; Spain [ 23 , 33 ], Finland [ 25 , 34 ], Israel [ 9 , 15 ], Turkey [ 22 , 24 , 35 38 ], Sweden [ 12 , 13 , 39 , 40 ], Norway [ 16 , 19 , 41 45 ], Belgium [ 17 , 18 , 45 , 46 ], United Kingdom [ 45 , 47 ], Netherlands [ 20 , 45 ], Denmark [ 45 , 48 ], Switzerland [ 45 ], Austria [ 45 ], Germany [ 45 ] and Italy [ 49 ]), America ( n = 8; Canada [ 21 , 26 , 50 ], USA [ 51 53 ] and Argentina [ 4 , 54 ]), Australia ( n = 5) [ 8 , 10 , 11 , 14 , 55 ]), and Taiwan ( n = 1) [ 56 , 57 ]. The results of quality appraisals of the included studies have been summarized in Supplementary Tables S1, S2 .…”
Section: Resultsmentioning
confidence: 99%
“…The results of quality appraisals of the included studies have been summarized in Supplementary Tables S1, S2 . A total of 38 (84%) studies had high [ 4 , 8 19 , 21 , 23 , 25 , 26 , 33 – 36 , 39 48 , 50 53 , 55 57 ], 7 (16%) had moderate quality [ 20 , 22 , 24 , 37 , 38 , 49 , 54 ], and no study had low quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation